Compositional and Structural Diversity of Woody Stands in the Community Forests of Rogho and Boala in Central-West Burkina Faso - Tiamiyu, Kasimou; Yanogo, Isidore Pawendkisgou; Nacoulma, et Blandine Marie Ivette (CV. Literasi Indonesia, 2023)
The biodiversity of community forests is poorly studied in Burkina Faso. This results in a lack of understanding of their ecological importance, which is characterized by neglect in their management. The main objective of this study is to characterize the flora and woody vegetation of the community forests of Rogho and Boala to demonstrate their importance. For this purpose, a forest inventory was conducted using stratified random sampling methods. Shannon, Simpson, Margalef, and Pielou diversity indices reveal significant biodiversity of the flora in both forests, with a better distribution of individuals within the species that make them up. The horizontal structure of the two woody populations is characterized by a predominance of individuals with small diameters (DBH € [5cm-25cm[) on either side, with respective regeneration rates of 58.36% and 22.46% for Rogho and Boala. Regarding the ecological importance of species, Lannea microcarpa has the highest Importance Value Index (IVI = 99.06) for the Rogho site, and Vitellaria paradoxa for the Boala site (IVI = 136.58). Phanerophytes dominate the flora of both forests with a strong presence of mesophanerophytes. The average density of woody plants is evaluated at 330.34 trees/ha and 742.01 trees/ha respectively in Rogho and Boala, with respective average land areas of 14.8 m2/ha and 119.78 m2/ha. This study highlights the strong ecological potential of the forests studied. Communal and regional authorities must develop strategies for the sustainable management of these forest areas.